Methodology for the improvement of hook shots, in the pioneer category boxers - Wilfredo Vázquez Calero; Giraldo Machuat Santana; Modesta Moreno Iglesias (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2020)
In boxing, precise actions are required in a very short period of time because, to the extent that the technical action in the attacks is faster, it makes it impossible to defend and counterattack efficiently during the fight. The objective of this work is to improve the technical preparation process in boxing from sports training, with emphasis on the execution of hook blows in the pioneer category boxers who train in the "Giraldo Córdova Cardín" boxing gym in Pinar del Río. It was based on the diagnosis of the state of this technical element, in the sample of ten athletes, in which the observation was applied to 24 training sessions, as well as an interview with the four boxing trainers who work with this category in that gym. A series of weaknesses were found when working with this technique in the training unit. As a final result, in order to make possible the correction of the existing deficiencies, a methodology containing a cognitive and an instrumental apparatus is implemented, methodological from the exercises that are presented and demonstrated to the coaches and the results in the competitions of the cycle 2019-2020 that show the quota of gain for the coaches and athletes.